Brand Image Memediasi Peran Content Marketing Dan Online Customer Review Terhadap Minat Beli Eatsambel - Fahimah, Mar’atul; Latifah, Umi (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2024)
Research aim : The purpose of this research is to identify the direct and indirect effects of content marketing and online customer reviews on purchase intention for Eatsambel Products on TikTok through brand image. Design/Methode/Approach : The method applied in this research is a quantitative approach that is associative in nature. Research Finding : The findings delineated within this investigation illustrate that content marketing exerts a discernible and affirmative influence on the brand image of Eatsambel Products on TikTok. Concurrently, online customer reviews similarly demonstrate a constructive and statistically significant impact on the aforementioned brand image. Furthermore, the study elucidates that content marketing significantly contributes to the augmentation of purchasing intent towards Eatsambel Products on TikTok. Conversely, the influence of online customer reviews on purchasing intent is not found to be statistically significant. Notably, brand image emerges as a pivotal determinant, exhibiting a positive and statistically significant association with purchasing intent concerning Eatsambel Products on TikTok, with brand image serving as an intermediary variable. Additionally, it is observed that content marketing, when considered alongside brand image as an intervening factor, does not exhibit a statistically significant impact on purchasing intent. Similarly, online customer reviews, when analyzed within the framework of brand image as an intervening variable, do not manifest a significant effect on purchasing intent regarding Eatsambel Products on TikTok. Theoretical contribution/Originality : This research proposes a conceptual model that investigates the interaction between content marketing, online customer reviews, and brand trust in influencing purchase intention of Eatsambel products holistically. Practitionel/Policy implication : This research provides valuable insights for Eatsambel to optimize content marketing strategies and online customer review management to strengthen brand trust, thereby increasing consumer buying interest in Eatsambel products. Research limitation : Limitations in this study include the focus on one product brand (Eatsambel), so the generalizability of the findings is limited to the specific context of that product.